Breast Self-Examination (BSE): Knowledge & Practice among Rural Women in Selected Area in Kishoreganj - Nurunnahar Afrin; Mohammad Kamruzzaman Khan; Jannat Ferdous (Central Medical College Journal, 2025)
Background: Breast cancer ranks as the most prevalent and lethal cancer affecting women globally, with increasing incidence rates observed in both developed and developing countries, including Bangladesh, where diagnoses often occur at advanced stages. Breast Self-Examination (BSE) is an easy, cost-effective, and accessible approach for early identification, particularly in settings with limited resources. Worldwide initiatives such as the WHO's breast cancer framework and national plans highlight the importance of early detection using BSE to lower mortality rates and enhance survival outcomes. Materials & Methods: A descriptive cross-sectional study was carried out using a purposefully chosen sample of 189 individuals from Mithamoin, Kishoreganj, Bangladesh. The researcher collected data through face-to-face interviews employing a 22-item standardized Breast Self-Examination scale focused on two areas: BSE Knowledge and Practice. Descriptive statistics, including frequency, percentages, means, and standard deviations, were utilized for data analysis. Results: The average age of the participants was 27.78 years, with a significant majority being Muslim (87.30%) and 29.63% lacking any formal education. Most participants (83.06%) were married, and large portions (74.07%) were housewives, with their average monthly family income being 22142.86 BDT. In this study, a vast majority of the participants demonstrated a poor level of knowledge (95.8%), while only 2.1% exhibited a good level of BSE practice. Conclusion: The research indicated that a majority of women lacked adequate understanding of Breast Self-Examination (BSE), including how to perform it, its significance, and the appropriate timing, with only a handful engaging in it on a regular basis. There is a pressing necessity to improve awareness and the practice of BSE to facilitate the early identification and prevention of breast cancer. Central Medical College Journal Vol 9 No 1 January 2025 Page: 12-17